Turning Sri Lanka's Urban Vision into Policy and Action - World Bank (Washington, DC, 2012)
Sri Lanka's country vision is to become a global hub between the East and the West and an upper middle-income country by 2016. Sri Lanka's urban vision, as defined in the government's development policy framework is to develop a system of competitive, environmentally sustainable, well-linked cities clustered in five metro regions and nine metro cities and to provide every family with affordable and adequate urban shelter by 2020. This policy note provides an initial assessment of Sri Lanka's urban characteristics, outlining the challenges ahead and broad policy directions for turning the urban vision into action. The policy note has six main sections. First section briefly outlines Sri Lanka's urban characteristics today. Second section discusses the main economic drivers of Sri Lanka's cities. Third section presents the main themes of Sri Lanka's Urban Vision (which includes the System of competitive cities vision and the adequate and affordable urban shelter for all vision) and discusses its economic rationale and viability given the urban characteristics and economic drivers of the country's cities. Fourth section outlines the main challenges for achieving the Urban Vision, based on the results of a diagnostic assessment carried out as an input to the policy note. Fifth section discusses recent government initiatives for implementing the urban vision, and how they have helped tackle the challenges. And sixth section offers broad policy directions and priority actions to achieve the Urban Vision.